2009
DOI: 10.1109/ted.2009.2032595
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown Voltage for Superjunction Power Devices With Charge Imbalance: An Analytical Model Valid for Both Punch Through and Non Punch Through Devices

Abstract: An analytical model for the electric field and the breakdown voltage (BV) of an unbalanced superjunction (SJ) device is presented in this paper. The analytical technique uses a superposition approach treating the asymmetric charge in the pillars as an excess charge component superimposed on a balanced charge component. The proposed double-exponentialmodel is able to accurately predict the electric field and the BV for unbalanced SJ devices in both punch through and non punch through conditions. The model is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 14 publications
0
35
0
Order By: Relevance
“…Although (4) and (5) are presented based on the punchthrough (PT) case, i.e., the drift region is fully depleted, they are also effective in calculating the breakdown voltage even for the nonpunchthrough (NPT) case, setting the unphysical negative electric field in the undepleted region to be zero [8]. From (5), the PT condition, i.e., when the electric field at A or B reaches zero [6], can be deduced as 0…”
Section: A Approximation Of the Electric Field Along The Electric Fimentioning
confidence: 99%
See 3 more Smart Citations
“…Although (4) and (5) are presented based on the punchthrough (PT) case, i.e., the drift region is fully depleted, they are also effective in calculating the breakdown voltage even for the nonpunchthrough (NPT) case, setting the unphysical negative electric field in the undepleted region to be zero [8]. From (5), the PT condition, i.e., when the electric field at A or B reaches zero [6], can be deduced as 0…”
Section: A Approximation Of the Electric Field Along The Electric Fimentioning
confidence: 99%
“…By substituting the electric field line expression (8) into (1) and (2), we get a simple and accurate approximation of the 2-D electric fields along the electric field line M CM , i.e., It is also shown that (9) is a good approximation for the electric field along the electric field line M CM .…”
Section: Approximation Of the Electric Field Along The Electric Fimentioning
confidence: 99%
See 2 more Smart Citations
“…The models that have previously been developed to understand the transient behavior of silicon PiN diodes during reverse recovery, including physics-based models [21], [22], analytical models [23]- [25], Saber Models [26] and PSPICE Models [27] are not extendable to SiC Schottky diodes since the latter is unipolar [28]. Models for parameter extraction in SiC Schottky diodes [29] provide valuable information about understanding the static behavior of the diodes, however, they lack the capability of modeling dynamic characteristics and switching energy.…”
Section: Index Terms-schottkymentioning
confidence: 99%